2017
DOI: 10.1371/journal.pone.0181722
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of the relationship between internet use, self-harm and suicidal behaviour in young people: The good, the bad and the unknown

Abstract: BackgroundResearch exploring internet use and self-harm is rapidly expanding amidst concerns regarding influences of on-line activities on self-harm and suicide, especially in young people. We aimed to systematically review evidence regarding the potential influence of the internet on self-harm/suicidal behaviour in young people.MethodsWe conducted a systematic review based on an electronic search for articles published between 01/01/2011 and 26/01/2015 across databases including Medline, Cochrane and PsychInf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
270
0
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(304 citation statements)
references
References 63 publications
5
270
0
13
Order By: Relevance
“…This research has ranged from exploration of the online environment itself (e.g. Biddle et al 2016) to a systematic review of the relationship between internet use and suicidal behaviour (Marchant et al 2017). The study by Biddle et al (2016) followed on from a similar study by the same researchers (Biddle et al 2008), which involved online searches for suicide-related information to determine the type of content that is likely to be accessed by suicidal internet users.…”
Section: Suicide and The Online Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This research has ranged from exploration of the online environment itself (e.g. Biddle et al 2016) to a systematic review of the relationship between internet use and suicidal behaviour (Marchant et al 2017). The study by Biddle et al (2016) followed on from a similar study by the same researchers (Biddle et al 2008), which involved online searches for suicide-related information to determine the type of content that is likely to be accessed by suicidal internet users.…”
Section: Suicide and The Online Environmentmentioning
confidence: 99%
“…A recent systematic review explored various aspects of the relationship between internet use and suicidal behaviour in young people (Marchant et al 2017). Examining literature published from 2011 to 2014, Marchant et al's review included 46 independent studies which reported a range of influences on suicidal behaviour.…”
Section: Suicide and The Online Environmentmentioning
confidence: 99%
“…Likewise, a recent review by Marchant et al. () showed that self‐harm or suicidal behavior was particularly associated with Internet addiction, high levels of Internet use, and Web sites with self‐harm or suicide content. Conversely, it was discussed that Internet use has the potential for isolation reduction and outreach, and may be a source of help and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring particular online media, such as social media, forums, or blogs, were smaller and provided lower quality evidence. Distressed online posts appear to be related to suicidal ideation and behavior in young people, but there is little evidence to suggest that social media use itself increases risk (Marchant et al, ).…”
Section: New Media Suicide and Suicide Contagionmentioning
confidence: 99%
“…Internet forums have been found to be supportive in terms of helping suicidal individuals find communities they could relate to, share their experiences with, and find mental health resources; however, there were also pro‐suicide forums that encouraged and normalized self‐harm and suicidal behaviors. Whether or not these exposures lead to suicidal behavior is still unclear and likely varies with individual circumstances (Marchant et al, ).…”
Section: Prevention and Intervention Opportunitiesmentioning
confidence: 99%